2011
DOI: 10.1248/bpb.34.379
|View full text |Cite
|
Sign up to set email alerts
|

Xiang-Qi-Tang Increases Avian Pathogenic Escherichia coli-Induced Survival Rate and Regulates Serum Levels of Tumor Necrosis Factor Alpha, Interleukin-1 and Soluble Endothelial Protein C Receptor in Chicken

Abstract: Xiang-Qi-Tang (XQT) is a Chinese herbal formula containing Rhizoma Cyperi, Andrographis paniculata and Astragalus membranaceus. The present study investigated the effects of XQT on the mortality and inflammatory mediators in a chicken model challenged with avian pathogenic Escherichia coli (APEC). To detect the effect of XQT, the chickens were pretreated with the formula 12 h before being challenged with 10 8 colony forming unit (CFU) of APEC. The results showed that 0.6 g/kg XQT significantly elevated the sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…TNF-α is the foremost inflammatory cytokine that activates the NF-κB pathway and upregulates the expression of other inflammatory cytokines, thereby stimulating and aggravating the inflammatory response ( Li et al, 2019 ; Yao et al, 2019 ). In addition, He et al (2011) found that APEC increased the serum levels of TNF-α and IL-1, leading to inflammation. In line with previous studies, this study showed that APEC infection in chicks induced the secretion of inflammatory cytokines, including TNF-α, IL-1β, IL-6, and IL-8.…”
Section: Discussionmentioning
confidence: 99%
“…TNF-α is the foremost inflammatory cytokine that activates the NF-κB pathway and upregulates the expression of other inflammatory cytokines, thereby stimulating and aggravating the inflammatory response ( Li et al, 2019 ; Yao et al, 2019 ). In addition, He et al (2011) found that APEC increased the serum levels of TNF-α and IL-1, leading to inflammation. In line with previous studies, this study showed that APEC infection in chicks induced the secretion of inflammatory cytokines, including TNF-α, IL-1β, IL-6, and IL-8.…”
Section: Discussionmentioning
confidence: 99%
“…The suppressed growth performance of animals bred in an unclean environment could be a result of intestinal dysfunction induced by bacterial challenge (1)(2)(3) . In this study, we confirmed the negative effects of E. coli challenge on growth performance of broilers, exhibited as reduced ABW, ADG and ADFI accompanied by an increased FCR.…”
Section: Discussionmentioning
confidence: 99%
“…Challenge by pathogenic Escherichia coli is responsible for a large variety of disorders in production, resulting in intestinal disruption and subsequent compromise in growth performance of chickens ( 1 3 ) . In the past few decades, antibiotics were widely used to prevent or control E. coli infection in animals.…”
mentioning
confidence: 99%
“…The principal pathogenic bacteria associated with poultry causing foodborne illnesses are Campylobacter , Salmonella , and Escherichia coli [1]. Escherichia coli can cause an enteric disease known as colibacillosis in chickens, which in turn results in a high mortality rate and huge economic loss in the poultry industry [2,3]. Although colibacillosis can be prevented or treated by the use of antibiotics, there exist controversies regarding the prophylactic use of antibiotics in livestock production throughout the world.…”
Section: Introductionmentioning
confidence: 99%